61 Superior irrigated lowland breeding lines with yield advantages of up to 22% identified in observational yield trials - CGIAR Research Program on Rice (2020)
1326 lines were evaluated in Observational yield trials in 2020 dry season and 61 lines superior to best checks Sahel 210 and Sahel 177 with 20 lines having yield advantage of 4-22% over best checks and good plant type